CLINICOEPIDEMIOLOGICAL FEATURES OF COVID-19 PATIENTS OF SECOND WAVE AT A TERTIARY CARE TEACHING HOSPITAL IN GUJARAT, INDIA - CHAWDA, HIREN M; HEDAMBA, RUTVIJ H; KOTHARI, NITIN; PANCHAL, KIRAN M (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The studies describing the clinicoepidemiological features of coronavirus disease-2019 (COVID-19) patients of first wave are available but about second wave very few studies have documented. This study was aimed to describe the clinicoepidemiological features and the causes of mortality of COVID-19 patients of second wave admitted in our center. Methods: This retrospective observational cross sectional study was carried out among 200 randomly selected and confirmed COVID-19 indoor patients admitted between 7th April, 2021 and 3rd July, 2021 in Dr. N. D. Desai Hospital, Nadiad. The demographic profile, clinical features, comorbidities, inflammatory markers and causes of mortality in these patients were analyzed. Results: A total 200 patients of COVID-19 of second wave were analyzed. Majority of them were males (64.5%) and the patients between 18 and 60 years of age constituted 60%. Hypertension (70.93%) and Diabetes mellitus (46.51%) were common comorbidities followed by ischemic heart diseases and chronic kidney disease. The most common presenting features were fever (75.7%), cough (68.8%), and shortness of breath (60%). The median duration of hospital stay was 7 days [interquartile range (IQR), 4–12]. The patients needed any kind of mode of oxygen therapy were 82.5%. The most common cause of death was cardiac arrest (70.58%) followed by severe acute respiratory distress syndrome ARDS (35.29%). Conclusions: In this retrospective study, most patients were young males with the age less than 60 years. The patients had one or more comorbidities, hypertension being the most common. Inflammatory markers were significantly higher in patients who died in our hospital.